Children's Understanding of the Fishing Profession: A Review of Perceptions, Motivations, and Required Skills - Suharyanto Suharyanto; Fitrinaldi Fitrinaldi; Rifai Irfan; Nevrita Nevrita; Izzati Nur; Abdulhajar Encik (SHS Web of Conferences)
This study aims to analyze children's understanding of the fishing profession in coastal areas, focusing on their perceptions, motivations, and the skills they perceive as essential for this occupation. A qualitative descriptive approach was employed, involving a survey of 100 children residing in coastal regions. The primary research instrument was a questionnaire covering various aspects such as risk perception, interest in the fishing profession, and relevant skills. The findings reveal that a majority of the respondents exhibited a low interest in pursuing a career in fishing. The primary reasons cited for this disinterest were income instability, high physical risks, and the demanding nature of the work. Consequently, strategies are needed to enhance the appeal of the fishing profession among the younger generation. These strategies could include skill-based training programs and awareness campaigns highlighting the profession's critical role in maintaining coastal ecosystem sustainability.